Religion, Spirituality, Well-Being, and Ill-Being in a Church-Renewal Movement: The Case of Finland - Hannikainen, Pietari (Journal of empirical theology, 2021)
An expanding body of research connects religiosity/spirituality (later R/S) with human well-being and health. While psychological and medical research lacks a common theoretical or theological framework, these dimensions are measured by instruments with a wide variation in quality. As the religious landscapes in Western societies are becoming increasingly plural and complex, the need for developing our understanding and assessment of the role of R/S in human health and well-being is as important as ever. This study, based on quantitative data (N = 529) from members of a church renewal oriented network in the Lutheran majority Church in Finland, measures the role of R/S in the subjective well-being of the participants through a multi-dimensional framework. While exploring Ellison’s Spiritual Well-being Scale (1983), the study expands its scope to a more multi-dimensional approach to religion, spirituality and well-being. The results reveal that religious beliefs and practices do not contribute to the level of subjective well-being in the lives of the participants as much as the way in which these beliefs and practices are lived out and actualized in social contexts. The study identified several sources of both well-being and ill-being in the participants’ lives. The article contributes to the terms of measuring the various ways in which R/S are connected to human well-being.